Peran Kepemimpinan Pimpinan Dayah dalam Membentuk Akhlak Santri di Dayah Raudhatul Qur’an Tungkob - Nur Fazillah; Anton Widyanto (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2019)
Leaders bear heavy responsibilities and play a significant role in management, and thus they should possess wisdom and skills in making innovations for the success of their work. This study aimed to investigate the following issues: the types of leadership applied by the head of Dayah Raudhatul Qur’an, the leadership role of the head of Dayah in the development of students’ behavior and the constraints faced by the leadership in the formation of morality students in Dayah Raudhatul Qur'an. The study employed a qualitative research design. Data were collected by observation, interview, and documentation. The results of the study showed that the types of leadership applied by the head of Dayah tended to follow the democratic, deliberative, and charimastic leadership. The role of the head of Dayah in terms of shaping the students’ behavior included establishing the regular Quran recitation, tausiah (giving advice), discipline, and dzikr (remembering Allah) after daily prayers. Further, the constraints faced by the leader in the formation of santri morality in Dayah Raudhatul Qur'an that is the influence from the outside because the majority of santri in Dayah Raudhatul Qur'an is a student from various universities and students are also busy by the tasks on campus so as not can focus on just one activity.